Comparison of Humoral Antibody Responses and Seroconversion Rates between Two Homologous ChAdOx1 nCoV-19 and mRNA-1273 Vaccination in Patients Undergoing Maintenance Hemodialysis - Shih-Hsin Hsiao; Yuh-Mou Sue; Chih-Chin Kao; Hui-Wen Chang; Yen-Chung Lin; Ching-Sheng Hung; Yi-Chen Hsieh; Shiao-Ya Hong; Chi-Li Chung; Jer-Hwa Chang; Ying-Shih Su; Ming-Che Liu; et al. (Vaccines, 2023)
Background: Hemodialysis patients are at an increased risk of SARS-CoV-2 infection and are excluded from preauthorization COVID-19 vaccine trials; therefore, their immunogenicity is uncertain. Methods: To compare the antibody responses to homologous ChAdOx1 and mRNA-1273 SARS-CoV-2 vaccination in hemodialysis patients, 103 age- and sex-matched hemodialysis patients with two homologous prime-boost vaccinations were recruited to detect anti-receptor-binding domain (RBD) IgG levels and seroconversion rates (SCRs) 14 days after a prime dose (PD14), before and 28 days after a boost dose (pre-BD0 and BD28). Results: Both mRNA-1273 and ChAdOx1 vaccinations elicited immunogenicity in study subjects, and the former induced higher anti-RBD IgG levels than the latter. The SCRs of both groups increased over time and varied widely from 1.82% to 97.92%, and were significantly different at PD14 and pre-BD0 regardless of different thresholds. At BD28, the SCRs of the ChAdOx1 group and the mRNA-1273 group were comparable using a threshold ≥ 7.1 BAU/mL (93.96% vs. 97.92%) and a threshold ≥ 17 BAU/mL (92.73% vs. 97.92%), respectively, but they were significantly different using a threshold ≥ 20.2% of convalescent serum anti-RBD levels (52.73% vs. 95.83%). The seroconversion (≥20.2% of convalescent level) at BD28 was associated with mRNA-1273 vaccination after being adjusted for age, sex, body mass index, and the presence of solicited reactogenicity after a prime vaccination. Conclusion: Our prospective, observational cohort indicates that a full prime-boost mRNA-1273 vaccination is likely to provide higher immune protection in hemodialysis patients compared to ChAdOx1, and this population with a prime-boost ChAdOx1 vaccination should be prioritized for a third dose.